Fort Riley and American Indians, 1853-1911 - James E. Sherow (Symphony in the Flint Hills, 2013)
The lure of the Army’s newest post for Indian peoples was irresistible as the following three stories illustrate. In the first instance, a party of well-armed Indians spied a rural farmstead located not far from Fort Riley, and they advanced toward the cabin alarming the occupants.
Keywords: Fort Riley; American Indians; military; army; buffalo hunt; George Catlin; Comanche; rural; farmstead; cabin; bison; hunting; tradition; Kaw Indians; Kansa; Junction City; tribe; Confederate; soldiers; Civil War; Custer; Black Kettle' s Camp; Fort Lyon; Colorado; wives; Smoky Hill River; First Dragoons; Ogden; Charles Schreyvogel; Cheyenne Expedition; Kiowa; Sioux; Samuel R. Curtis; Fort Leavenworth; Kansas; Indian Territory; Dog Soldiers; Potawatomis; Shawnee; Delaware; treaty; Arapaho; government; horses; captured; raid; territorial